Selling the value of data with a customer-centric approach : case Vaisala - Laakkonen, Aki (2023)
The significance of big data for businesses is increasing rapidly along with its quantity. The research around utilizing big data as an external, sellable resource is gaining more and more interest. This has enabled the emerge of a completely new business model: selling data products. However, the value of data is a complex matter, and the research around value-based selling of data products is still lacking. This study aims to contribute to the practical understanding of utilizing the means of value-based selling in the context of data products. The study discusses the value perception of data products and efficient communication of the value to B2B customers. The key concepts considered in this study are big data, data value, perceived value, value-creation, and value-based selling, which form the conceptual framework to understand the value-based selling of data products. This study adopts the qualitative research method and is abductive in nature. Data was collected by conducting three semi-structured interviews. The respondents of the study represent the customer perspective and they are product management professionals working in data-reliant logistics optimization. The findings of the research were analyzed using a thematic analysis method. The findings of the study contribute to development of a better understanding of how value-based selling approach can be applied in the context of selling data products. The findings support value-based selling as a sales approach on data products. However, as a notification, this study suggests that the value-based selling approach on data products should incorporate a very precise communication of value for the customer. Customers may wish to solve a specific operational challenge by inputting new data source, and the supplier must help the customer to understand how the data can be turned into such insights that the customer is competent to put into use.